2019
DOI: 10.1177/0021998319880282
|View full text |Cite
|
Sign up to set email alerts
|

Use of a chain extender as a dispersing agent of the CaCO3 into PBAT matrix

Abstract: This paper investigates the effect of the incorporation of chain extender on the poly(butylene adipate -co-terephthalate) (PBAT) and their mixture with calcium carbonate (CaCO3) composites. Chain extender (ADR) was used to enhance the compatibility between PBAT and CaCO3, which have poor interfacial adhesion. Mechanical, thermal, and morphological properties of PBAT, PBAT/chain extender, and their composites were studied. The incorporation of the chain extender enhanced Young’s modulus and elongation at break … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…10 showed that the Young's modulus and yield strength of PBAT/P34HB/A‐CB composites were increased significantly with increasing CB content. de Nunes et al 43 . investigated the effect of chain extender on PBAT/calcium carbonate (CaCO 3 ) composites and found that the Young's modulus of PBAT/CaCO 3 /chain extender (79.5/20/0.5) increased by 23.5% and tensile strength decreased by 26.1% compared with neat PBAT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 showed that the Young's modulus and yield strength of PBAT/P34HB/A‐CB composites were increased significantly with increasing CB content. de Nunes et al 43 . investigated the effect of chain extender on PBAT/calcium carbonate (CaCO 3 ) composites and found that the Young's modulus of PBAT/CaCO 3 /chain extender (79.5/20/0.5) increased by 23.5% and tensile strength decreased by 26.1% compared with neat PBAT.…”
Section: Resultsmentioning
confidence: 99%
“…10 showed that the Young's modulus and yield strength of PBAT/P34HB/A-CB composites were increased significantly with increasing CB content. de Nunes et al 43 investigated the effect of chain extender on PBAT/calcium carbonate (CaCO 3 ) composites and found that the Young's modulus of PBAT/CaCO 3 /chain extender (79.5/20/0.5) increased by 23.5% and tensile strength decreased by 26.1% compared with neat PBAT. It was reported by Pinheiro et al 44 that the elasticity modulus of PBAT/cellulose nanocrystals modified with octadecyl isocyanate (MCNC) composites increased from 55.7 MPa for neat PBAT to 79.2 MPa for the nanocomposite with 7 wt% MCNC, and tensile stress decreased from 22.0 to 12.4 MPa.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…24 Currently, it is mainly modified by blending with other materials to produce different kinds of films for agriculture, food, and other industries. 25–29 However, it has not been applied for the wastewater treatment. Its structure is depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A final advantage of the inclusion of particulate fillers in biodegradable polymers is that in general, the overall cost price of these materials is substantially lowered compared to unfilled polymers. Although the main academic focus of biodegradable polymer reinforcement in recent years has been on the use of organic natural fillers [18][19][20], the use of inorganic mineral fillers such as talc [21,22], calcium carbonate [23,24], kaolin [25,26], and mica [27,28] and their impact on the biodegradability of these polymers [29][30][31] has been investigated as well. As the properties of particulate polymer composites can highly fluctuate strongly, due to variations in additional polymer additives, processing techniques, and the applied test methods, it is generally complex to compare individually reported results [32][33][34].…”
Section: Introductionmentioning
confidence: 99%